2015
DOI: 10.1111/eth.12359
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Artificial Stimuli in Behavioral Research: Making the Case for Egg Rejection Studies in Avian Brood Parasitism

Abstract: 24 25 Experimentation is at the heart of classical and modern behavioral ecology research. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 45 publications
(74 reference statements)
5
59
1
Order By: Relevance
“…We employed multiple experimental treatments because use of some particular egg types may fail to reveal a realistic picture of host egg discrimination abilities (Hauber et al 2015). First, for puncture ejecter hosts hard plastic model eggs may be impossible to eject (Martín-Vivaldi et al 2002).…”
Section: Egg Experimentsmentioning
confidence: 99%
“…We employed multiple experimental treatments because use of some particular egg types may fail to reveal a realistic picture of host egg discrimination abilities (Hauber et al 2015). First, for puncture ejecter hosts hard plastic model eggs may be impossible to eject (Martín-Vivaldi et al 2002).…”
Section: Egg Experimentsmentioning
confidence: 99%
“…These studies assess chromatic reflectance and/or pattern data to characterize how the tetrachromatic avian visual system assesses the foreign eggshell's appearance (Avilés et al 2010 ;Stoddard and Stevens 2011 ;Hanley et al 2013 ;Igic et al 2012 ;Poláček et al 2013 ;Stoddard et al 2014 ), and have repeatedly confirmed long-standing conclusions that foreign eggs are rejected more often when they are perceived as more dissimilar to the hosts' own eggs (Cassey et al 2008 ;Spottiswoode and Stevens 2010 ;Stevens et al 2013 ;Croston and Hauber 2014 ;Hauber et al 2015 ; Fig. 1 ).…”
Section: Aq4mentioning
confidence: 98%
“…a The relationship between egg rejection rates and egg-egg contrasts plotted as the mean just noticeable differences (JNDs) between unmanipulated host eggs versus dyed host eggs, unmanipulated eggs of the cuckoo, and unmanipulated other conspecifics of the hosts (data replotted from Hauber et al 2015 ). b The relationship between egg-nest contrast, plotted as the mean JNDs between unmanipulated host nest lining However, egg rejection behaviours of hosts are also influenced by the physical and biotic properties of the nest environment.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations